2008
DOI: 10.2514/1.27467
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Generation by an Open Shock Tube

Abstract: We perform experimental and numerical studies of a shock tube with an open end. The purpose is to investigate the impulse due to the exhaust of gases through the open end of the tube as a model for a partially filled detonation tube as used in pulse detonation engine testing. We study the effects of the pressure ratio (varied from 3 to 9.2) and the volume ratio (expressed as fill fractions) between the driver and driven section. Two different driver gases, helium and nitrogen, and fill fractions between 5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…Numerical analysis by Morris et al [23] and an experiment by Copper et al [33] showed that the expansion effect of by nozzle became dominant, like a steady flow, if the ambient pressure around a PDE was sufficiently low. Kasahara et al [34] showed the physical essence of the partial-fill effect in an experiment with a shock-tube-shaped ballistic pendulum and by numerical analysis. Not only the above-mentioned fundamental studies but also validations of PDE systems have been carried out as application studies.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical analysis by Morris et al [23] and an experiment by Copper et al [33] showed that the expansion effect of by nozzle became dominant, like a steady flow, if the ambient pressure around a PDE was sufficiently low. Kasahara et al [34] showed the physical essence of the partial-fill effect in an experiment with a shock-tube-shaped ballistic pendulum and by numerical analysis. Not only the above-mentioned fundamental studies but also validations of PDE systems have been carried out as application studies.…”
Section: Introductionmentioning
confidence: 99%
“…This essence of the partial fill effect is explained by considering shock impedance. 16,25) If the shock impedance of the driven gas is higher than the detonation wave, the transmitted and reflected waves are both shock waves. The reflected shock wave undergoes repeated reflection between the contact surface and the closed end wall, and the impulse increases.…”
Section: Propellant-based Specific Impulsementioning
confidence: 99%
“…Kasahara et al 16) compared single-pulse experimental and numerical calculation results using an open shock tube and the bubble model (He and air, N 2 and air). When the fill fraction was small ( < 0:2), the analytical model predicted a maximum specific impulse.…”
Section: Propellant-based Specific Impulsementioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to investigate the local ignitions behind shock waves under low temperature conditions, from the point of view of chemical kinetics in high-prssure (non-diluted test gases) shock tube experiments in which the non-uniformity of reflected shock waves tends to be greater because of increased viscous effects [23,24] and from the view of application systems (for example, pulse detonation engines (PDEs) [25][26][27][28][29][30][31][32][33][34][35] etc.). Therefore we focused on local ignitions induced by non-uniformity behind reflected shock waves under low-temperature conditions (Voevodsky and Soloukhin [17] : mild ignition, Gilbert and Strehlow [2] : hot spot initiation, Mayer and Oppenheim [18] : mild ignition) and investigated numerically and experimentally the local ignition position and the reason why local ignitions are located at a point distant from the reflecting wall.…”
Section: Objective Of the Present Studymentioning
confidence: 99%